DISKURSUS KELISANAN AL-QUR’AN: MEMBUKA RUANG BARU - Alwi HS, Muhammad; Hamid, Nur (UIN Walisongo Semarang, 2019)
This paper is about to discuss discourse as the identity of the Qur'an which is now in the form of writing (Mushaf). In its history, the Qur'an is present in an environment that is familiar with oral traditions, delivered in oral form from the Prophet (speaker) to the Arab community (listeners). Based on the oral delivery, the Al-Qur'an indicates to be examined in the discourse discourse. The result of this paper is the discourse on the oral level of the Qur'an and even the naming as the Qur'an. Until the Qur'an takes the form of a text (mushaf) which is met today by Muslims, but the structure of orality can still be found clearly. With the structure of orality, it certainly presents a specific understanding of orality, as was the revelation understood by the Prophet Muhammad as a speaker and the Arab community as opposed to speech. The occurrence of understanding between the Prophet Muhammad and the Arab Society gives an understanding that the Qur'an contains understanding at that time, so that if there is an inertia, then the Arab community will question the purpose of the verse delivered. From this, the context that is presented in the discourse of oral Qur'an is a clear context, which binds the speaker and listener, or also commonly referred to as contextual.